Gut Microbiota Composition in Prediabetes and Newly Diagnosed Type 2 Diabetes: A Systematic Review of Observational Studies - Geetha Letchumanan; Nizam Baharom; Blair Lawley; Mohd Rahman Omar; Fathima Begum Syed Mohideen; Natasya Abdullah; Marlini Muhamad; Faizul Helmi Addnan; Nur Fariha Mohd Manzor; Zarini Ismail; Siva Gowri a/p Pathmanathan (Frontiers Media S.A., 2024)
Indexed by WOS/Scopus/ERA